Integration of occupational health and safety management, social responsibility of business, and sustainability: A stakeholder-based qualitative study on China’s electric power industry - Song Yu (SHS Web of Conferences, 2023)
Improving working conditions and promoting the health, safety and well-being of workers are highly relevant to the social responsibility of business and the sustainability of enterprises. This empirical study investigates the successes and barriers of the integration of occupational health and safety management (OHSM), corporate social responsibility (CSR), and sustainability in China’s electric power industry, with the combined theoretical framework of New St. Gallen Management Model and stakeholder theory. Semi-structured interviews were carried out among the internal, external and distal stakeholders (n=90), supplemented with on-the-spot observations. Through statistical and discourse analysis, it is found that the integration of OHSM, CSR, and sustainability has been achieved at the structural, operational, and organizational levels in China’s electric power industry, due to the fast development of technology and the legal system ensuring a good environmental sphere, with people-centered philosophy being highlighted. However, some deficiencies such as law reenforcement and the coherence between internal and external stakeholder management systems must be improved, particularly with respect to frontline workforce training. The communication of OHSM, CSR, and sustainability outside of the industry should also be enhanced for a better environmental sphere and public support.